Prisoners of Geography: Ten maps that tell you everything you need to know about global politics - Henrico, Ivan (Scientia Militaria - South African Journal of Military Studies, 2020)
Tim Marshall is an esteemed authority on foreign affairs, with more than thirty years’ experience in broadcasting, reporting, analysis and writing about past, present and future geopolitical affairs – most of the time reporting from the front line on major world events and conflict zones that had significant geopolitical effects on global politics, such as the Balkan wars of the 1990s, the Kosovo crisis of 1999, the first Gulf War (1991), the US war in Afghanistan (2001). He also covered three US presidential elections (The What and The Why, 2016). Prisoners of geography: Ten maps that tell you everything you need to know about global politics is arguably the most successful of his books, and makes for an intriguing read by an author with such an impressive résumé.